Some new solutions of the (3+1)-Dimensional Jimbo-Miwa equation via the improved (G'/G)-Expansion method - Naher, Hasibun; Aini Abdullah, Farah; Rashid, Abdur (© 2014 Eudoxus Press, LLC, 2016)
This article was published in the Journal of Computational Analysis and Applications [© 2014 Eudoxus Press, LLC ] the article link is : http://eds.b.ebscohost.com/eds/detail/detail?sid=b7811ecb-026d-4434-96bb-47ca700cd41d%40sessionmgr105&vid=0&hid=108&bdata=JnNpdGU9ZWRzLWxpdmU%3d#AN=92883167&db=aph